Targeting Hepatocellular Carcinoma: What did we Discover so Far? - Brito, Ana Filipa (2016)
Hepatocellular carcinoma (HCC) is increasingly considered an issue of global importance. Its rates of incidence and mortality have been markedly increasing over the last decades. Among risk factors, some should be highlighted, namely the infections by hepatitis B and C virus, as well as clinical cases of cirrhosis. HCC is characterized as asymptomatic disease in the initial stages which most often leads to a late diagnosis. At molecular and genetic level HCC represents a highly complex tumor entity, including a wide variety of mutations, thus accounting for different mechanisms of resistance towards therapeutic approaches. In particular, mutations of the TP53 gene, as well as a deregulation between the expression of pro- and anti-apoptotic proteins of the BCL-2 family are observed. Regarding treatment modalities, surgical procedures offer the best chance of cure, however, due to a late diagnosis, most of concerned patients cannot be subjected to them. Chemotherapy and radiotherapy are also ineffective, and currently, the treatment with sorafenib is the most commonly used systemic therapy although it can only increase the patient survival for some months. In this sense, a quick and accurate investigation is of utmost importance in order to develop ways of early diagnosis as well as new therapies for HCC.